Corporate contact tracing as a pandemic response. Issue 1 (1st January 2022) - French, Martin; Guta, Adrian; Gagnon, Marilou; Mykhalovskiy, Eric; Roberts, Stephen L; Goh, Su; McClelland, Alexander; McKelvey, Fenwick
ABSTRACT: Since the start of the COVID-19 pandemic, a steady stream of propositions from tech giants and start-ups alike has furnished us with the idea that GPS- or Bluetooth-enabled contact tracing apps are a vital part of the pandemic response. This commentary considers these apps as 'corporate contact tracing', emphasizing the private-sector role that such developments imply. We first discuss corporate contact tracing's potential to de-center the power of public health authorities. Then, using the frames of surveillance capitalism and disaster capitalism, we suggest how corporate contact tracing might feed the rise of corporate power in the public sphere. We question its capacity to address structural inequalities and to foster a social justice vision of public health. And, we wonder whether corporate contact tracing might intensify the effects of discriminatory design and algorithmic oppression. We conclude by calling for a discussion of this technology beyond questions of privacy and efficacy.